The Orientalisation of North Africa: New hints from the study of autosomal STRs in an Arab population - Sarra Elkamel; Lotfi Cherni; Luis Alvarez; Sofia L. Marques; Maria J. Prata; Sami Boussetta; Amel Benammar-Elgaaied; Houssein Khodjet- (Taylor & Francis Group, 2017)
Background: Recent genomic analyses suggest that the current North African gene pool was mainly influenced by population flow coming from the East that altered the genetic structure of autochthonous Berber populations. Such genetic flow has not been extensively addressed yet using North African populations of Middle-eastern origin as reference. Aim: To discern the Middle-eastern component in the genetic background of Tunisian Arabs and evaluate the extent of gene flow from the Middle East into North African autochthonous Berber populations. Subjects and methods: This study has examined 113 Tunisians of well-known Arabian origin from Kairouan region, using 15 autosomal Short Tandem Repeats (STRs) loci. Results: No deviations from Hardy-Weinberg equilibrium were observed and all loci presented high levels of heterozygosity. Principal coordinate and STRUCTURE analyses were consistent in clustering together North African and Middle Eastern populations, likely reflecting the recent gene flow from the East dating back to the Arab conquest period. This demographic migration and the Arabisation process that submerged the original Berber language and customs seems to have be accompanied by substantial gene flow and genetic admixture. Conclusion: This study represents an additional step to obtain a comprehensive understanding of the complex demographic history of North African populations.